The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10620-011-1590-5
|View full text |Cite
|
Sign up to set email alerts
|

Methane on Breath Testing Is Associated with Constipation: A Systematic Review and Meta-analysis

Abstract: We demonstrate that methane present on breath testing is significantly associated with constipation in both IBS and functional constipation. These results suggest there may be merit in using breath testing in constipation. Moreover, methane may be used to identify candidates for antibiotic treatment of constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 45 publications
12
103
3
8
Order By: Relevance
“…It is important to consider the above fi ndings using an evidencebased medicine approach. A recent meta-analysis evaluated the existing literature comparing the presence of methane and constipation ( 31 ). Although not all studies have confi rmed these results, most do to support a signifi cant association.…”
Section: Is There a Role For Methane In Constipation-predominant Irrimentioning
confidence: 99%
“…It is important to consider the above fi ndings using an evidencebased medicine approach. A recent meta-analysis evaluated the existing literature comparing the presence of methane and constipation ( 31 ). Although not all studies have confi rmed these results, most do to support a signifi cant association.…”
Section: Is There a Role For Methane In Constipation-predominant Irrimentioning
confidence: 99%
“…In a meta-analysis of 1277 IBS patients, we found that methane was associated with constipation, with a pooled OR=3.51 (CI=2.00-6.16) [25]. Further, treatment with the non-absorbable antibiotics neomycin and rifaximin both eliminates methane and improves constipation [26], particularly in C-IBS subjects with successful eradication of methane on breath test (Pimentel et al, submitted), suggesting that methane itself is the cause of the constipation.…”
Section: Introductionmentioning
confidence: 97%
“…34,36 Methane production as a diagnostic test has been shown to be very accurate in predicting IBS-C, with a sensitivity of 91% and a specificity of 81.3%. 33 Two earlier studies support that methane is associated with the severity of IBS-C, 33,39 and although methane does not account for all IBS-C patients, a meta-analysis including a total of 1277 subjects (319 methane producers and 958 methane non-producers) showed that methane is significantly associated with IBS-C. 40 Another study demonstrated that methane-producing IBS subjects had small bowel movements, straining, lactose intolerance, and weight loss. 34 Furthermore, objective measures of constipation tracking stool habits showed that the degree of methane production on LBT correlated with the severity of constipation.…”
Section: -mentioning
confidence: 99%